Ceruloplasmin and Hypoferremia: Studies in Burn and Non-Burn Trauma Patients - Michael A. Dubick; Johnny L. Barr; Carl L. Keen; James L. Atkins (Antioxidants, 2015)
Objective: Normal iron handling appears to be disrupted in critically ill patients leading to hypoferremia that may contribute to systemic inflammation. Ceruloplasmin (Cp), an acute phase reactant protein that can convert ferrous iron to its less reactive ferric form facilitating binding to ferritin, has ferroxidase activity that is important to iron handling. Genetic absence of Cp decreases iron export resulting in iron accumulation in many organs. The objective of this study was to characterize iron metabolism and Cp activity in burn and non-burn trauma patients to determine if changes in Cp activity are a potential contributor to the observed hypoferremia. Material and Methods: Under Brooke Army Medical Center Institutional Review Board approved protocols, serum or plasma was collected from burn and non-burn trauma patients on admission to the ICU and at times up to 14 days and measured for indices of iron status, Cp protein and oxidase activity and cytokines. Results: Burn patients showed evidence of anemia and normal or elevated ferritin levels. Plasma Cp oxidase activity in burn and trauma patients were markedly lower than controls on admission and increased to control levels by day 3, particularly in burn patients. Plasma cytokines were elevated throughout the 14 days study along with evidence of an oxidative stress. No significant differences in soluble transferrin receptor were noted among groups on admission, but levels in burn patients were lower than controls for the first 5 days after injury. Conclusion: This study further established the hypoferremia and inflammation associated with burns and trauma. To our knowledge, this is the first study to show an early decrease in Cp oxidase activity in burn and non-burn trauma patients. The results support the hypothesis that transient loss of Cp activity contributes to hypoferremia and inflammation. Further studies are warranted to determine if decreased Cp activity increases the risk of iron-induced injury following therapeutic interventions such as transfusions with blood that has undergone prolonged storage in trauma resuscitation.